Health problems among IT professionals in Chennai city, Tamil Nadu - Vyas, Smita (International Journal Of Community Medicine And Public Health, 2019)
Background: Increasing technological advantage lead to the higher health disadvantages to IT professionals who spent most of the time working in front of the computer. They are experiencing many neural, visual and musculoskeletal ailments. The present study was done with the aim to limelight the health issues among IT employees in IT Park, Chennai. Methods: This cross-sectional quantitative survey related to health issues among IT professionals was done on 417 employees of Chennai IT Park during the period from January 2018 to May 2018. The predesigned questionnaire included socio-demographic and health related issues. It was sent to the employees through various media including Facebook messenger, LinkedIn private messaging and email. The data was analyzed and presented in number and percentages and the related associations were analysed by Chi square test. Results: The prevalence of pain in eye was the major visual problem noticed in 157 (38%) patients and the rate of incidence was similar in both males and females. About 50% of the participants had pain/stiffness in lower back. Feeling nervous ness is the related stress condition experienced by the respondents (49%). Other health correlated issues noticed among the participants was headache (40%). The prevalence rate of these factors was higher in males compared to females. Conclusions: The study concluded that IT professionals face several health issues in terms of visual, musculoskeletal and stress problems in Chennai IT Park.